Silk fibroin‐based scaffolds for bone regeneration1. Issue 2 (2nd November 2012) - Kuboyama, Noboru; Kiba, Hideo; Arai, Kiyoshi; Uchida, Ryoichiro; Tanimoto, Yasuhiro; Bhawal, Ujjal K.; Abiko, Yoshimitsu; Miyamoto, Sayaka; Knight, David; Asakura, Tetsuo; Nishiyama, Norihiro
Abstract: Porous scaffolds were prepared using regenerated Bombyx mori silk fibroin dissolved in water or hexafluoroisopropanol (HFIP). The effects of these two preparations on the formation and growth of new bone on implantation into the rabbit femoral epicondyle was examined. The aqueous‐based fibroin (A‐F) scaffold exhibited significantly greater osteoconductivity as judged by bone volume, bone mineral content, and bone mineral density at the implant site than the HFIP‐based fibroin (HFIP‐F) scaffold. Micro‐CT analyses showed that the morphology of the newly formed bone differed significantly in the two types of silk fibroin scaffold. After 4 weeks of implantation, new trabecular bone was seen inside the pores of the A‐F scaffold implant while the HFIP‐F scaffold only contained necrotic cells. No trabecular bone was seen within the pores of the latter scaffolds, although the pores of these did contain giant cells and granulation tissue. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.